2005
DOI: 10.1021/bi048662e
|View full text |Cite
|
Sign up to set email alerts
|

α1-Antitrypsin Polymerization:  A Fluorescence Correlation Spectroscopic Study

Abstract: Alpha(1)-antitrypsin (AT) is the most abundantly circulating human proteinase inhibitor in the serpin family. The polymerization of AT, leading to alpha(1)-antitrypsin deficiency, has been studied extensively in vitro by a variety of ensemble methods. Here we report the use of fluorescence correlation spectroscopy to gain further insight into this process. Measurements of the distributions of diffusion times of polymerizing AT, carried out at 45, 50, and 55 degrees C, clearly show the existence of a kinetic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…␣ 1 -AT polymers were labeled with deuterium for different time periods to investigate the stability and solvent accessibility of monomers within the polymers in a region-specific manner. Because dissociation of the polymer occurs much slower than our deuterium labeling time (as a previous study demonstrated (19)), dilution of the polymeric sample into D 2 O does not affect the structural integrity of the polymer within our experimental time scale. Fig.…”
Section: Structure and Dynamics Of The Monomeric Intermediate Pre-mentioning
confidence: 76%
“…␣ 1 -AT polymers were labeled with deuterium for different time periods to investigate the stability and solvent accessibility of monomers within the polymers in a region-specific manner. Because dissociation of the polymer occurs much slower than our deuterium labeling time (as a previous study demonstrated (19)), dilution of the polymeric sample into D 2 O does not affect the structural integrity of the polymer within our experimental time scale. Fig.…”
Section: Structure and Dynamics Of The Monomeric Intermediate Pre-mentioning
confidence: 76%
“…6,7 The patent b-sheet A then accepts the reactive loop of a second a 1 -antitrypsin molecule to form a dimer, which can extend into chains of reactive center loop-b-sheet A polymers. 2,6,[8][9][10][11][12] The recent crystal structure of a dimer of another serpin, antithrombin, demonstrated a linkage between a b-hairpin of the reactive loop and strand 5A of one molecule and b-sheet A of another. This dimer was used as the basis of a novel model for the polymer in which helix I is unravelled and the proteins are linked by a b-hairpin containing the reactive center loop and strand 5A.…”
mentioning
confidence: 99%
“…This perturbation in structure allows the formation of an unstable intermediate (M Ã ) and a sequential β-strand linkage between the reactive center loop of one molecule and β-sheet A of another (Fig. 1A) (3)(4)(5)(6)(7)(8). However this model has recently been challenged by the crystal structure of a self-terminating dimer of another serpin, antithrombin (9).…”
mentioning
confidence: 99%